Kaji Prospek Pemanfaatan Sistem Pembangkit Listrik Hibrida Energi Angin dan Matahari di Desa Langi Kepulauan Simeulue - Anan Niazi Usman; Ahmad Syuhada; Hamdani Hamdani (Jurnal Teknik Mesin Unsyiah, 2015)
Langi is a rural area in Simeulue distric having not yet received electricity by national grid. To enhance daily activity of Langi villager in term oflighting and utilities, local diesel generators used as main power. Increasing fuel cost effect to production cost of diesel generator. Since this type of power source is not viable option economically.This study investigates feasibility of hybrid system to provide electricity in Langi. The hybrid system uses combination of diesel generator, solar panels and wind turbines. Meteorology Agency reports wind speedaverage 3-3.67 m/sec at 10 meters above sea level and daily average radiation about 2.5-4.5 kWh/m2/day. Those data used as initial input to simulated power hybrid system using HOMER software. The simulation results show that appropriate combination applied in Langi is a unit of solar panels 55 kW, 10 unit wind turbines with the capacity 30 kW, 2 unit diesel generators with capacity 110 kW and 30 kW, and a 40 kW inverter. Refer to Langi village electricity demand around 220.807 kWh/year, so electricity producing by the hybrid system able to supply around 399 088 kWh/year.